(untitled) - Beck, Jessica (New York, 2012)
The Testbuilder for the TOEIC Tests offers three complete tests for the Listening & Reading TOEIC test, followed by three tests for the Speaking TOEIC test and three tests for the Writing TOEIC test.
Keywords: English language,English language,Tiếng Anh; Examinations,Study guides,Textbooks for foreign speakers,Bài thi,Hướng dẫn học